Coated cutting tool

The coating cutting tool with a tailored alternating laminate structure addresses the challenges of wear resistance and toughness, extending tool life and improving machining efficiency in high-speed and high-feed applications.

JP2025044622AActive Publication Date: 2025-04-02TUNGALOY CORP

Patent Information

Application Number
JP2023152311
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

Existing coating cutting tools face challenges in achieving both high wear resistance and toughness during high-speed machining and high-feed machining, leading to limited tool life and increased costs.

Method used

A coating cutting tool with a specific configuration, featuring a substrate and a coating layer with a first alternating laminate structure composed of layers A and B. Layer A contains a compound with the composition (Al a Cr b Ti 1-a-b)N, and layer B contains a compound with the composition (Al c Ti 1-c-d B d)N, optimized atomic ratios and thicknesses to enhance hardness, thermal stability, and toughness.

Benefits of technology

The tool life of the coated cutting tool is extended in both high-speed machining and high-feed machining, achieving improved wear resistance, thermal shock resistance, and defect resistance, which reduces costs and enhances machining efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044622000001_ABST
    Figure 2025044622000001_ABST
Patent Text Reader

Abstract

To provide a coated cutting tool which can extend a tool life in both high speed working and high feed working.SOLUTION: A coated cutting tool includes a base material, and a coating layer formed on the base material, wherein the coating layer has a first alternately laminated structure that two or more layers A and layers B are alternately formed, the layer A contains (AlaCrbTi1-a-b)N, the layer B contains (AlcTi1-c-dBd)N, average thickness of the first alternately laminated structure is 0.50 μm or more and 10.00 μm or less, and average thickness per one layer of each of the layers A and the layers B in the first alternately laminated structure is 2 nm or more and 300 nm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coated cutting tool. [Background technology]

[0002] Conventionally, cutting tools made of cemented carbide or sintered cubic boron nitride (cBN) have been widely used for cutting steel, etc. Among them, surface-coated cutting tools that include one or more hard coatings such as TiN layer, TiAlN layer, TiCrN layer on the surface of cemented carbide substrate are used for various machining due to their high versatility.

[0003] For example, Patent Document 1 discloses a surface-coated cutting tool including a tool substrate and a coating layer, the coating layer having a thickness of 0.2 to 10.0 μm and including a structure in which at least one first layer and one second layer are alternately laminated, the at least one first layer having an average thickness of 0.5 to 100.0 nm, and a surface-coated cutting tool having a surface-coated cutting tool including a tool substrate and a coating layer. x Ti 1-x-y-z M y ) B z N (wherein M is one or more elements selected from Groups 4, 5, and 6 of the periodic table and the lanthanides, x is 0.100 to 0.640, y is 0.001 to 0.100, and z is 0.060 to 0.400), and the at least one second layer has an average thickness of 0.5 to 100.0 nm and is represented by the formula: (Al p Cr 1-p-q-r M' q ) B r A surface-coated cutting tool has been proposed, characterized in that it has an average composition represented by M′=1, M′=0.650-0.900, q=0.000-0.100, and r=0.000-0.050.

[0004] Also, for example, in Patent Document 2, there is a coated cutting tool including a cemented carbide body and a PVD coating. The cemented carbide body has a composition of 5 to 18 wt% Co, 0.1 to 2.5 wt% Cr, 0 to 10 wt% of carbides or carbonitrides (other than WC) of metals in Groups 4, 5, and 6 of the periodic table of elements, and the balance WC. The PVD coating has an average composition of Ti a Al b Cr c N (a = 0.25 to 0.7, b = 0.3 to 0.7, and c = 0.01 to 0.2, a + b + c = 1), which is a (Ti, Al, Cr)N nano-layered PVD coating. The PVD coating is a nano-layered PVD coating A / B / A / B / A ···, where the sub-layer A is Ti u Al v Cr w N (u = 0.1 to 0.4, v = 0.5 to 0.8, w = 0.01 to 0.3, u + v + w = 1), the sub-layer B is Ti x Al y Cr z N (x = 0.4 to 0.7, y = 0.3 to 0.6, z = 0 to 0.2, x + y + z = 1, u < x and v > y), respectively. The thickness of the nano-layered PVD coating is 0.5 to 10 μm. A coated cutting tool has been proposed.

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Patent Document 2

Summary of the Invention

Problems to be Solved by the Invention

[0006] In recent years, there has been a strong demand for labor-saving, energy-saving, and cost-saving in cutting processes, and therefore coated cutting tools are required to have performance that can withstand more efficient processing. For example, there is a trend toward higher speeds and / or higher feed rates for more efficient processing, but the performance required of coated cutting tools varies greatly under these conditions.

[0007] In high-speed machining, the materials used in coated cutting tools must be hard and wear-resistant, and must also have improved thermal shock resistance at high temperatures and be able to suppress embrittlement caused by material deterioration. On the other hand, in high-feed machining, the load on the tool tip tends to be large, so the materials used in coated cutting tools must have high toughness.

[0008] In general, it is difficult to achieve both the properties required for a coated cutting tool in high-speed machining and high-feed machining, and therefore a coated cutting tool suitable for each machining is usually selected and used. On the other hand, achieving and enhancing both of these properties is preferable from the viewpoint of reducing costs, since one type of coated cutting tool can be used to handle various machining conditions.

[0009] The surface-coated cutting tool of Patent Document 1 has a coating layer in which a first layer containing element B and a second layer that may not contain element B are alternately laminated, and has excellent thermal shock resistance in high-speed machining. However, the surface-coated cutting tool of Patent Document 1 has insufficient thermal stability and toughness in the coating layer near the interface between the first layer and the second layer, and there is room for further improvement. For the above reasons, the surface-coated cutting tool of Patent Document 1 has room for improvement in both fracture resistance in high-speed machining and fracture resistance in high-feed machining.

[0010] In addition, the coated cutting tool of Patent Document 2 has a coating layer in which sub-layers A and B are alternately laminated, and has excellent fracture resistance in high-feed machining. On the other hand, the coated cutting tool of Patent Document 2 has an insufficient hardness because the coating layer does not contain element B, and has insufficient thermal shock resistance in high-speed machining because layers containing element B and layers not containing element B are not alternately laminated. For these reasons, the coated cutting tool of Patent Document 2 has room for improvement in wear resistance and fracture resistance in high-speed machining.

[0011] The present invention has been made in consideration of the above circumstances, and has an object to provide a coated cutting tool that can extend the tool life in both high-speed cutting and high-feed cutting. [Means for solving the problem]

[0012] The inventors conducted extensive research into extending the tool life of coated cutting tools and discovered that by giving the coated cutting tool a specific configuration, it is possible to extend the tool life in both high-speed machining and high-feed machining, which led to the completion of the present invention.

[0013] That is, the gist of the present invention is as follows. [1] A coated cutting tool comprising a substrate and a coating layer formed on the substrate, The coating layer has a first alternating laminate structure in which two or more A layers and two or more B layers are alternately formed, The layer A contains a compound having a composition represented by the following formula (1): (Al a Cr b Ti 1-a-b )N (1) (In formula (1), a is the content (atomic ratio) of Al element with respect to the total content of Al element, Cr element, and Ti element, 0.50≦a≦0.68 is satisfied, b is the content (atomic ratio) of Cr element with respect to the total of Al element, Cr element, and Ti element, 0.02≦b≦0.30 is satisfied, 1-ab is the content (atomic ratio) of Ti element to the total content of Al element, Cr element, and Ti element, 0.11≦1-ab≦0.40 is satisfied.) The layer B contains a compound having a composition represented by the following formula (2): (Al c Ti 1-c-d B d )N (2) (In formula (2), c is the content (atomic ratio) of Al element with respect to the total content of Al element, Ti element, and B element, 0.30≦c≦0.64 is satisfied, d is the content ratio (atomic ratio) of B element to the total of Al element, Ti element, and B element, 0.01≦d≦0.10 is satisfied, 1-cd is the content (atomic ratio) of Ti element to the total content of Al element, Ti element, and B element, 0.30≦1-cd≦0.69 is satisfied.) The average thickness of the first alternating laminate structure is 0.50 μm or more and 10.00 μm or less, the average thickness per layer of the A layer in the first alternating laminate structure is 2 nm or more and 300 nm or less; The average thickness per layer of the B layer in the first alternating laminate structure is 2 nm or more and 300 nm or less. Coated cutting tools. [2] a ratio ((1-ab) / d) of a content ratio (atomic ratio) of Ti element in the A layer to a content ratio (atomic ratio) of B element in the B layer is 2.0 or more and 25.0 or less; [1] A coated cutting tool according to the present invention. [3] the average value ((a+c) / 2) of the content ratio (atomic ratio) of Al element in the A layer and the content ratio (atomic ratio) of Al element in the B layer is 0.50 or more and 0.62 or less; A coated cutting tool according to [1] or [2]. [4] The coating layer further has a second alternating laminate structure in which the A layer and the C layer are alternately formed in two or more layers, The C layer contains a compound having a composition represented by the following formula (3): (Al e Ti 1-e )N (3) (In formula (3), e is the content (atomic ratio) of Al element with respect to the total content of Al element and Ti element, 0.30≦e≦0.64 is satisfied, 1-e is the content ratio (atomic ratio) of Ti element to the total of Al element and Ti element, 0.36≦1-e≦0.70 is satisfied.) The average thickness of the second alternating laminate structure is 0.50 μm or more and 5.00 μm or less, the average thickness per layer of the A layer in the second alternating laminate structure is 2 nm or more and less than 30 nm; The average thickness per layer of the C layer in the second alternate laminate structure is 2 nm or more and less than 30 nm. The coated cutting tool according to any one of [1] to [3]. [5] The average thickness per layer of the A layer in the first alternating laminate structure is 30 nm or more and 300 nm or less, The average thickness per layer of the B layer in the first alternating laminate structure is 30 nm or more and 300 nm or less. The coated cutting tool according to any one of [1] to [4]. [6] the coating layer has a third alternating laminate structure in which the first alternating laminate structure and the second alternating laminate structure are alternately formed three or more times in total, The average thickness per structure of the first alternating laminate structure in the third alternating laminate structure is 0.1 μm or more and 1.5 μm or less, The average thickness per structure of the second alternating laminate structure in the third alternating laminate structure is 0.1 μm or more and 1.5 μm or less. [4] A coated cutting tool according to the present invention. [7] In the X-ray diffraction of the first alternating stack structure, the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic (200) plane to the diffraction peak intensity (I(200)) of the cubic (111) plane is 0.5 or more and 5.0 or less. The coated cutting tool according to any one of [1] to [6]. [8] In the X-ray diffraction of the third alternating stack structure, the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic (111) plane to the diffraction peak intensity (I(200)) of the cubic (200) plane is 0.5 or more and 5.0 or less. [6] A coated cutting tool according to the present invention. [9] The coating layer has an upper layer on a surface of the first alternating laminate structure or the third alternating laminate structure opposite to the substrate, the upper layer is a single layer or multiple layers of a compound consisting of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and at least one element selected from the group consisting of C, N, O, and B (however, the composition of the compound constituting the upper layer is different from the composition of the compound constituting the layer of the first alternating laminate structure or the second alternating laminate structure that is in contact with the upper layer); The average thickness of the upper layer is 0.01 μm or more and 2.00 μm or less. The coated cutting tool according to any one of [1] to [8].

[10] The coating layer has a lower layer between the substrate and the first alternating laminate structure or the third alternating laminate structure, the lower layer is a single layer or multiple layers of a compound consisting of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and at least one element selected from the group consisting of C, N, O, and B (however, the composition of the compound constituting the lower layer is different from the composition of the compound constituting the layer of the first alternating laminate structure or the second alternating laminate structure that is in contact with the lower layer); The average thickness of the lower layer is 0.01 μm or more and 2.00 μm or less. The coated cutting tool according to any one of [1] to [9].

[11] The average thickness of the entire coating layer is 0.5 μm or more and 10.0 μm or less; The coated cutting tool according to any one of [1] to

[10] . Effect of the Invention

[0014] According to the present invention, it is possible to provide a coated cutting tool capable of extending the tool life in both high speed machining and high feed machining. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic diagram showing an example of a coated cutting tool of the present invention. FIG. [Diagram 2] FIG. 4 is a schematic view showing another example of a coated cutting tool of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] A detailed description will be given below of an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment"); however, the present invention is not limited to the present embodiment. Various modifications of the present invention are possible without departing from the gist of the present invention. In the drawings, the same elements are given the same reference numerals, and duplicated explanations will be omitted. Furthermore, unless otherwise specified, the positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings. Furthermore, the dimensional ratios of the drawings are not limited to those shown in the drawings.

[0017] The coated cutting tool of the present embodiment is a coated cutting tool including a substrate and a coating layer formed on the substrate, The coating layer has a first alternating laminate structure in which two or more A layers and two or more B layers are alternately formed, Layer A contains a compound having a composition represented by the following formula (1): (Al a Cr b Ti 1-a-b )N (1) (In formula (1), a is the content (atomic ratio) of Al element with respect to the total content of Al element, Cr element, and Ti element, 0.50≦a≦0.68 is satisfied, b is the content (atomic ratio) of Cr element with respect to the total of Al element, Cr element, and Ti element, 0.02≦b≦0.30 is satisfied, 1-ab is the content (atomic ratio) of Ti element to the total content of Al element, Cr element, and Ti element, 0.11≦1-ab≦0.40 is satisfied.) Layer B contains a compound having a composition represented by the following formula (2): (Al c Ti 1-c-d B d )N (2) (In formula (2), c is the content (atomic ratio) of Al element with respect to the total content of Al element, Ti element, and B element, 0.30≦c≦0.64 is satisfied, d is the content ratio (atomic ratio) of B element to the total of Al element, Ti element, and B element, 0.01≦d≦0.10 is satisfied, 1-cd is the content (atomic ratio) of Ti element to the total content of Al element, Ti element, and B element, 0.30≦1-cd≦0.69 is satisfied.) The average thickness of the first alternating laminate structure is 0.50 μm or more and 10.00 μm or less, The average thickness of each of the A layers in the first alternating laminate structure is 2 nm or more and 300 nm or less; The average thickness per layer of the B layers in the first alternate laminate structure is 2 nm or more and 300 nm or less.

[0018] The factors that enable such a coated cutting tool to have a long tool life in both high-speed cutting and high-feed cutting are not clearly understood in detail, but are presumed to be as follows, although the factors are not limited to the following. In the A layer forming the first alternating laminate structure, the composition represented by formula (1) (Al a Cr b Ti1-a-b When the content ratio a of the Al element in N is 0.50 or more, the hardness and oxidation resistance are increased, and the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the content ratio a of the Al element is 0.68 or less, the formation of hexagonal crystals is suppressed, so that the hardness is increased, the coated cutting tool has excellent wear resistance in high-speed machining, and the thermal stability in the vicinity of the interface between the A layer and the B layer is improved, which has the effect of improving thermal shock resistance, and furthermore, the chipping resistance in high-speed machining of the coated cutting tool is improved. In addition, in the A layer forming the first alternate laminate structure, the composition represented by formula (1) (Al a Cr b Ti 1-a-b When the content ratio b of the Cr element in N is 0.02 or more, the formation of hexagonal crystals is suppressed, so that the hardness is increased and the coated cutting tool has excellent wear resistance in high-speed machining, and the thermal stability in the vicinity of the interface between the A layer and the B layer is improved, which has the effect of improving thermal shock resistance, and further, the chipping resistance in high-speed machining of the coated cutting tool is improved. On the other hand, when the content ratio b of the Cr element is 0.30 or less, the toughness is improved and the chipping resistance in both high-speed machining and high-feed machining of the coated cutting tool is improved. In addition, in the A layer forming the first alternate laminate structure, the composition represented by formula (1) (Al a Cr b Ti 1-a-b When the Ti content (1-ab) in )N is 0.11 or more, the thermal stability of the interface between the A layer and the B layer is improved, the thermal shock resistance is improved, and peeling of the coating layer and the progression of cracks to the base material during cutting are suppressed, so that the coated cutting tool has excellent chipping resistance in high-speed machining. On the other hand, when the Ti content (1-ab) is 0.40 or less, when the Al content a is relatively large, the hardness is increased and the oxidation resistance is improved, so that the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the Cr content b is relatively large, the formation of hexagonal crystals is suppressed, so that the hardness is increased and the coated cutting tool has excellent wear resistance in high-speed machining. Next, in the B layer forming the first alternate laminate structure, the composition represented by formula (2) (Al c Ti 1-c-d Bd When the content ratio c of the Al element in N is 0.30 or more, the hardness and oxidation resistance are increased, and the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the content ratio c of the Al element is 0.64 or less, the formation of hexagonal crystals is suppressed, so that the hardness is increased, the coated cutting tool has excellent wear resistance in high-speed machining, and the thermal stability in the vicinity of the interface between the A layer and the B layer is improved, which has the effect of improving thermal shock resistance, and furthermore, the chipping resistance in high-speed machining of the coated cutting tool is improved. In addition, the B layer forming the first alternate laminate structure has a composition represented by formula (2) (Al c Ti 1-c-d B d When the content ratio d of the B element in N is 0.01 or more, the hardness is high and the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the content ratio d of the B element is 0.10 or less, the toughness is improved and the chipping resistance in both high-speed machining and high-feed machining of the coated cutting tool is improved. In addition, the B layer forming the first alternate laminate structure has a composition represented by formula (2) (Al c Ti 1-c-d B d When the Ti content (1-cd) in )N is 0.30 or more, the thermal stability of the interface between the A layer and the B layer is improved, the thermal shock resistance is improved, and peeling of the coating layer and the progression of cracks to the base material during cutting are suppressed, so that the coated cutting tool has excellent chipping resistance in high-speed machining. On the other hand, when the Ti content (1-cd) is 0.69 or less, when the Al content c is relatively large, the hardness is increased and the oxidation resistance is improved, so that the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the B content d is relatively large, the hardness is increased and the coated cutting tool has excellent wear resistance in high-speed machining. In addition, the coated cutting tool of this embodiment has a first alternating laminate structure in which two or more layers A and two or more layers B each containing a compound having such a specific composition are alternately formed, thereby improving thermal shock resistance and providing excellent chipping resistance during high-speed machining. Furthermore, when the average thickness of the first alternating laminate structure is 0.50 μm or more, the wear resistance of the coated cutting tool during high-speed machining is improved, whereas when the average thickness of the first alternating laminate structure is 10.00 μm or less, peeling of the coating layer can be suppressed, and the chipping resistance of the coated cutting tool during both high-speed machining and high-feed machining is improved. In addition, when the average thickness of each of the A and B layers in the first alternating laminate structure is 2 nm or more, the effect of suppressing the progression of cracks generated during processing to the base material is improved, and the chipping resistance of the coated cutting tool is improved in both high-speed and high-feed processing. On the other hand, when the average thickness of each of the A and B layers in the first alternating laminate structure is 300 nm or less, the effect of having an alternating laminate structure consisting of two different layers is obtained, the hardness is increased, and the coated cutting tool has excellent wear resistance in high-speed processing, and further, the effect of suppressing the progression of cracks generated during processing to the base material is obtained, and further, the chipping resistance of the coated cutting tool is improved in both high-speed and high-feed processing. Due to the combination of these effects, the coated cutting tool of this embodiment can extend the tool life in both high-speed machining and high-feed machining.

[0019] The coated cutting tool of this embodiment includes a substrate and a coating layer formed on the substrate. The substrate used in this embodiment is not particularly limited as long as it can be used as the substrate of the coated cutting tool. Examples of the substrate include cemented carbide, cermet, ceramics, cubic boron nitride sintered body, diamond sintered body, and high-speed steel. Among them, it is more preferable that the substrate is one or more selected from the group consisting of cemented carbide, cermet, ceramics, and cubic boron nitride sintered body, since the wear resistance and chipping resistance of the coated cutting tool are further excellent.

[0020] In the coated cutting tool of this embodiment, the average thickness of the entire coating layer is preferably 0.5 μm or more and 10.0 μm or less. In the coated cutting tool of this embodiment, when the average thickness of the entire coating layer is 0.5 μm or more, the wear resistance of the coated cutting tool in high-speed machining is improved. In addition, in the coated cutting tool of this embodiment, when the average thickness of the entire coating layer is 10.0 μm or less, the chipping resistance is further improved in both high-speed machining and high-feed machining, mainly due to the suppression of peeling of the coating layer. From the same viewpoint, the average thickness of the entire coating layer is more preferably 0.6 μm or more and 9.6 μm or less, and even more preferably 1.2 μm or more and 7.8 μm or less.

[0021] [First alternate laminated structure] In the coated cutting tool of this embodiment, the coating layer has a first alternating laminate structure in which two or more layers A and two or more layers B are alternately formed. The coated cutting tool of this embodiment has an improved thermal shock resistance due to the first alternating laminate structure in which two or more layers A and two or more layers B containing a compound having a specific composition are alternately formed, and therefore has excellent chipping resistance during high-speed machining.

[0022] [A layer] In the coated cutting tool of this embodiment, the layer A is a compound layer containing a compound having a composition represented by the following formula (1). (Al a Cr b Ti 1-a-b )N (1) (In formula (1), a is the content (atomic ratio) of Al element with respect to the total content of Al element, Cr element, and Ti element, 0.50≦a≦0.68 is satisfied, b is the content (atomic ratio) of Cr element with respect to the total of Al element, Cr element, and Ti element, 0.02≦b≦0.30 is satisfied, 1-ab is the content (atomic ratio) of Ti element to the total content of Al element, Cr element, and Ti element, 0.11≦1-ab≦0.40 is satisfied.)

[0023] In the A layer forming the first alternating laminate structure, the composition represented by formula (1) (Al a Cr b Ti 1-a-b When the content ratio a of the Al element in )N is 0.50 or more, the hardness is increased and the oxidation resistance is improved, and the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the content ratio a of the Al element is 0.68 or less, the formation of hexagonal crystals is suppressed, so that the hardness is increased, the coated cutting tool has excellent wear resistance in high-speed machining, and the thermal stability in the vicinity of the interface between the A layer and the B layer is improved, which has the effect of improving thermal shock resistance, and furthermore, the chipping resistance in high-speed machining of the coated cutting tool is improved. From the same viewpoint, (Al a Cr b Ti 1-a-b The content ratio a of Al element in N is preferably 0.51 or more and 0.67 or less, and more preferably 0.55 or more and 0.66 or less.

[0024] In addition, in the A layer forming the first alternate laminate structure, the composition represented by formula (1) (Al a Cr b Ti 1-a-b When the content ratio b of the Cr element in )N is 0.02 or more, the formation of hexagonal crystals is suppressed, so that the hardness is increased and the coated cutting tool has excellent wear resistance in high-speed machining. In addition, the thermal stability in the vicinity of the interface between the A layer and the B layer is improved, and the effect of improving thermal shock resistance is obtained, and further, the chipping resistance in high-speed machining of the coated cutting tool is improved. On the other hand, when the content ratio b of the Cr element is 0.30 or less, the toughness is improved and the chipping resistance in both high-speed machining and high-feed machining of the coated cutting tool is improved. From the same viewpoint, when the content ratio b of the Cr element in (Al a Cr b Ti 1-a-b The content ratio b of Cr element in N is preferably 0.03 or more and 0.29 or less, and more preferably 0.04 or more and 0.25 or less.

[0025] In addition, in the A layer forming the first alternate laminate structure, the composition represented by formula (1) (Al a Cr b Ti 1-a-bWhen the Ti content (1-ab) in )N is 0.11 or more, the thermal stability of the interface between layers A and B is improved, the thermal shock resistance is improved, and peeling of the coating layer and the progression of cracks to the base material during cutting are suppressed, so that the coated cutting tool has excellent chipping resistance in high-speed machining. On the other hand, when the Ti content (1-ab) is 0.40 or less, when the Al content a is relatively large, the hardness is increased and the oxidation resistance is improved, so that the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the Cr content b is relatively large, the formation of hexagonal crystals is suppressed, so that the hardness is increased and the coated cutting tool has excellent wear resistance in high-speed machining. From the same viewpoint, (Al a Cr b Ti 1-a-b The content ratio of Ti element in N (1-ab) is preferably 0.12 or more and 0.38 or less, and more preferably 0.15 or more and 0.36 or less.

[0026] In this embodiment, the composition of each compound layer is, for example, (Al 0.60 Cr 0.20 Ti 0.20 When expressed as )N, it means that the content ratio (atomic ratio) of Al element to the total of Al element, Cr element, and Ti element is 0.60, the content ratio (atomic ratio) of Cr element to the total of Al element, Cr element, and Ti element is 0.20, and the content ratio (atomic ratio) of Ti element to the total of Al element, Cr element, and Ti element is 0.20. In other words, it means that the amount of Al element to the total of Al element, Ti element, Al element, Cr element, and Ti element is 60%, the amount of Cr element to the total of Al element, Cr element, and Ti element is 20%, and the amount of Ti element to the total of Al element, Cr element, and Ti element is 20%.

[0027] [B layer] In the coated cutting tool of this embodiment, layer B is a compound layer containing a compound having a composition represented by the following formula (2). (Al c Ti 1-c-d B d )N (2) (In formula (2), c is the content (atomic ratio) of Al element with respect to the total content of Al element, Ti element, and B element, 0.30≦c≦0.64 is satisfied, d is the content ratio (atomic ratio) of B element to the total of Al element, Ti element, and B element, 0.01≦c≦0.10 is satisfied, 1-cd is the content (atomic ratio) of Ti element to the total content of Al element, Ti element, and B element, 0.30≦1-cd≦0.69 is satisfied.)

[0028] In the B layer forming the first alternating laminate structure, the composition represented by formula (2) (Al c Ti 1-c-d B d When the content ratio c of the Al element in )N is 0.30 or more, the hardness is increased and the oxidation resistance is improved, and the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the content ratio c of the Al element is 0.64 or less, the formation of hexagonal crystals is suppressed, so that the hardness is increased, the coated cutting tool has excellent wear resistance in high-speed machining, and the thermal stability in the vicinity of the interface between the A layer and the B layer is improved, which has the effect of improving thermal shock resistance, and furthermore, the chipping resistance in high-speed machining of the coated cutting tool is improved. From the same viewpoint, (Al c Ti 1-c-d B d The content ratio c of Al element in N is preferably 0.31 or more and 0.63 or less, and more preferably 0.33 or more and 0.56 or less.

[0029] In addition, the B layer forming the first alternate laminate structure has a composition represented by formula (2) (Al c Ti 1-c-d B d When the content ratio d of the B element in )N is 0.01 or more, the hardness is high and the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the content ratio d of the B element is 0.10 or less, the toughness is improved and the chipping resistance of the coated cutting tool in both high-speed machining and high-feed machining is improved. From the same viewpoint, (Al c Ti 1-c-d B dThe content ratio d of the B element in N is preferably 0.02 or more and 0.09 or less, and more preferably 0.02 or more and 0.07 or less.

[0030] In addition, the B layer forming the first alternate laminate structure has a composition represented by formula (2) (Al c Ti 1-c-d B d When the content ratio (1-cd) of Ti element in )N is 0.30 or more, the thermal stability of the interface between the A layer and the B layer is improved, the thermal shock resistance is improved, and peeling of the coating layer and the progression of cracks to the base material during cutting are suppressed, so that the coated cutting tool has excellent chipping resistance in high-speed machining. On the other hand, when the content ratio (1-cd) of Ti element is 0.69 or less, when the content ratio c of Al element is relatively large, the hardness is increased and the oxidation resistance is improved, so that the coated cutting tool has excellent wear resistance in high-speed machining. On the other hand, when the content ratio d of B element is relatively large, the hardness is increased and the coated cutting tool has excellent wear resistance in high-speed machining. From the same viewpoint, when the content ratio (Al c Ti 1-c-d B d The content ratio of Ti element in N (1-cd) is preferably 0.32 or more and 0.67 or less, and more preferably 0.37 or more and 0.65 or less.

[0031] In the coated cutting tool of this embodiment, when a lower layer described later is not formed, it is preferable to first form the A layer on the surface of the substrate. In the coated cutting tool of this embodiment, when the A layer is first formed on the surface of the substrate, the adhesion between the substrate and the coating layer tends to be improved.

[0032] In the coated cutting tool of this embodiment, the number of repetitions of the A layer and the B layer in the first alternate laminate structure is 2 or more, preferably 5 to 500, and more preferably 6 to 96. In this embodiment, when one layer A and one layer B are formed, the "number of repetitions" is one.

[0033] In the coated cutting tool of this embodiment, the average thickness of the first alternating laminate structure is 0.50 μm or more and 10.00 μm or less. When the average thickness of the first alternating laminate structure is 0.50 μm or more, the wear resistance of the coated cutting tool in high-speed machining is improved. On the other hand, when the average thickness of the first alternating laminate structure is 10.00 μm or less, peeling of the coating layer can be suppressed, and the chipping resistance of the coated cutting tool in both high-speed machining and high-feed machining is improved. From the same viewpoint, the average thickness of the first alternating laminate structure is preferably 0.60 μm or more and 9.60 μm or less, and more preferably 1.20 μm or more and 7.80 μm or less. In this embodiment, the average thickness of the first alternating laminate structure described herein is the sum of the average thicknesses of the multiple first alternating laminate structures when the first alternating laminate structures and the second alternating laminate structures are formed alternately, for example, as in the third alternating laminate structure described below.

[0034] In the coated cutting tool of this embodiment, the average thickness of each of the A layer and the B layer in the first alternating laminate structure is 2 nm or more and 300 nm or less. In the first alternating laminate structure, when the average thickness of each of the A layer and the B layer is 2 nm or more, the effect of suppressing the progression of cracks generated during processing to the base material is improved, and the chipping resistance of the coated cutting tool in both high-speed processing and high-feed processing is improved. On the other hand, in the first alternating laminate structure, when the average thickness of each of the A layer and the B layer is 300 nm or less, the effect of having an alternating laminate structure consisting of two different layers is obtained, the hardness is increased, and the coated cutting tool has excellent wear resistance in high-speed processing, and further, the effect of suppressing the progression of cracks generated during processing to the base material is obtained, and further, the chipping resistance of the coated cutting tool in both high-speed processing and high-feed processing is improved. From the same viewpoint, the average thickness of each of the A layer and the B layer in the first alternating laminate structure is preferably 3 nm or more and 280 nm or less, more preferably 5 nm or more and 150 nm or less. In the first alternate laminate structure, the average thickness per layer of the A layer and the average thickness per layer of the B layer may be the same or different.

[0035] In the first alternate laminate structure, the ratio ((1-ab) / d) of the content (atomic ratio) of Ti element in the A layer to the content (atomic ratio) of B element in the B layer is preferably 2.0 or more and 25.0 or less. In the first alternating laminate structure, when the ratio ((1-ab) / d) of the content ratio (atomic ratio) of Ti element in the A layer to the content ratio (atomic ratio) of B element in the B layer is 2.0 or more, the thermal stability near the interface between the A layer and the B layer is improved, and the effect of improving thermal shock resistance is likely to be obtained. In addition, the chipping resistance in high-speed machining of the coated cutting tool is also likely to be improved. Furthermore, the toughness near the interface between the A layer and the B layer is also likely to be improved, and the chipping resistance in high-feed machining of the coated cutting tool is also likely to be improved. On the other hand, in the first alternating laminate structure, when the ratio ((1-ab) / d) is 25.0 or less, the effect of improving thermal shock resistance due to the coating layer having the first alternating laminate structure is likely to be high, and the chipping resistance in high-speed machining of the coated cutting tool is also likely to be improved. From the same viewpoint, the ratio ((1-ab) / d) is more preferably 2.4 or more and 24.0 or less, and even more preferably 3.0 or more and 13.0 or less.

[0036] In the first alternate laminate structure, the average value ((a+c) / 2) of the content (atomic ratio) of Al element in the A layer and the content (atomic ratio) of Al element in the B layer is preferably 0.50 or more and 0.62 or less. In the first alternating laminate structure, when the average value ((a+c) / 2) of the content ratio (atomic ratio) of the Al element in the A layer and the content ratio (atomic ratio) of the Al element in the B layer is 0.50 or more, the hardness tends to be high and the oxidation resistance tends to be improved, and the wear resistance of the coated cutting tool in high-speed machining tends to be improved. On the other hand, in the first alternating laminate structure, when the average value ((a+c) / 2) is 0.62 or less, the formation of hexagonal crystals is suppressed, so the hardness tends to be high, the wear resistance of the coated cutting tool in high-speed machining tends to be improved, and further, the thermal stability near the interface between the A layer and the B layer tends to be improved, the thermal shock resistance tends to be further increased, and the chipping resistance of the coated cutting tool in high-speed machining tends to be further improved. From the same viewpoint, the average value ((a+c) / 2) is more preferably 0.51 or more and 0.61 or less, and even more preferably 0.53 or more and 0.60 or less.

[0037] [Second alternate laminated structure] In the coated cutting tool of this embodiment, it is preferable that the coating layer further has a second alternate laminate structure in which the A layers and the C layers are alternately formed in two or more layers. The layer C in the second alternate laminate structure contains a compound having a composition represented by the following formula (3). (Al e Ti 1-e )N (3) (In formula (3), e is the content (atomic ratio) of Al element with respect to the total content of Al element and Ti element, 0.30≦e≦0.64 is satisfied, 1-e is the content ratio (atomic ratio) of Ti element to the total of Al element and Ti element, 0.36≦1-e≦0.70 is satisfied.) The layer A in the second alternating laminate structure is the same as the layer A in the first alternating laminate structure. When the second alternating laminate structure is formed on the surface of the first alternating laminate structure facing the substrate, the adhesion between the coating layer and the substrate tends to be further improved. Also, when the second alternating laminate structure is formed on the surface of the first alternating laminate structure facing the substrate, or when the second alternating laminate structure is formed between two first alternating laminates, the effect of suppressing the progression of cracks generated during processing to the substrate tends to be further improved. For the reasons described above, in the coated cutting tool of this embodiment, when the coating layer has the second alternating laminate structure, fracture resistance tends to be further improved in both high-speed machining and high-feed machining.

[0038] [C layer] In the coated cutting tool of this embodiment, the C layer is a compound layer containing a compound having the composition represented by the above formula (3). In the C layer forming the second alternating laminate structure, the composition represented by formula (3) (Al e Ti 1-e When the content ratio e of the Al element in )N is 0.30 or more, the hardness and oxidation resistance tend to be increased, and the wear resistance in high-speed machining of the coated cutting tool tends to be improved. On the other hand, in the C layer forming the second alternating laminate structure, the composition represented by formula (3) (Al e Ti 1-e When the content ratio e of the Al element in )N is 0.64 or less, the formation of hexagonal crystals is suppressed, so that the hardness tends to be high and the wear resistance of the coated cutting tool during high-speed machining tends to be improved. From the same viewpoint, the composition represented by formula (3) (Al e Ti 1-e The content ratio e of Al element in N is preferably 0.35 or more and 0.60 or less, and more preferably 0.40 or more and 0.55 or less. In addition, in the C layer forming the second alternate laminate structure, the composition represented by formula (3) (Al e Ti 1-e When the content ratio (1-e) of Ti element in )N is 0.36 or more, the formation of hexagonal crystals is suppressed, so that the hardness tends to be high and the wear resistance of the coated cutting tool during high-speed machining tends to be improved. On the other hand, in the C layer forming the second alternating laminate structure, the composition represented by formula (3) (Ale Ti 1-e When the content ratio (1-e) of Ti element in )N is 0.70 or less, the hardness and oxidation resistance tend to be increased, and the wear resistance during high-speed machining of the coated cutting tool tends to be improved. From the same viewpoint, the composition represented by formula (3) (Al e Ti 1-e The content ratio of Ti element in N (1-e) is preferably 0.40 or more and 0.65 or less, and more preferably 0.45 or more and 0.60 or less.

[0039] In the coated cutting tool of this embodiment, the number of repetitions of the A layer and the C layer in the second alternate laminate structure is 2 or more, preferably 5 to 250, and more preferably 6 to 75. In this embodiment, when one layer A and one layer C are formed, the "number of repetitions" is one.

[0040] In the coated cutting tool of this embodiment, the average thickness of the second alternating laminate structure is preferably 0.50 μm or more and 5.00 μm or less. When the average thickness of the second alternating laminate structure is 0.50 μm or more, the wear resistance of the coated cutting tool in high-speed machining tends to improve. On the other hand, when the average thickness of the second alternating laminate structure is 5.00 μm or less, peeling of the coating layer can be suppressed, and the chipping resistance of the coated cutting tool in both high-speed machining and high-feed machining tends to be further improved. From the same viewpoint, the average thickness of the second alternating laminate structure is preferably 0.60 μm or more and 4.50 μm or less, and more preferably 1.00 μm or more and 3.00 μm or less. In this embodiment, the average thickness of the second alternating laminate structure described herein is, for example, the sum of the average thicknesses of the multiple second alternating laminate structures when the first alternating laminate structures and the second alternating laminate structures are formed alternately, such as in the third alternating laminate structure described below.

[0041] In the coated cutting tool of this embodiment, the average thickness of each of the A layer and the C layer in the second alternating laminate structure is preferably 2 nm or more and less than 30 nm. In the second alternating laminate structure, when the average thickness of each of the A layer and the C layer is 2 nm or more, the effect of suppressing the progression of cracks generated during processing to the base material is improved, and the chipping resistance of the coated cutting tool in both high-speed processing and high-feed processing tends to be improved. On the other hand, in the second alternating laminate structure, when the average thickness of each of the A layer and the C layer is less than 30 nm, the decrease in adhesion due to the residual stress difference between the first alternating laminate structure and the second alternating laminate structure is suppressed, and peeling is suppressed, so that the chipping resistance of the coated cutting tool in both high-speed processing and high-feed processing tends to be further improved. From the same viewpoint, the average thickness of each of the A layer and the C layer in the second alternating laminate structure is preferably 3 nm or more and 27 nm or less, and more preferably 4 nm or more and 25 nm or less. In the second alternate laminate structure, the average thickness per layer of the A layer and the average thickness per layer of the C layer may be the same or different. The average thickness of each layer forming the first alternating laminate structure is preferably larger than the average thickness of each layer forming the second alternating laminate structure. The first alternating laminate structure containing the B element is prone to large residual stress. For this reason, the average thickness of each layer forming the first alternating laminate structure is made larger than the average thickness of each layer forming the second alternating laminate structure, and more preferably, the average thickness of each layer is set to the above-mentioned range, so that the residual stress difference between the first alternating laminate structure and the second alternating laminate structure tends to be reduced. In such a case, specifically, for example, the average thickness of each layer of the A layer and the B layer in the first alternating laminate structure is preferably 30 nm or more and 300 nm or less. When the average thickness of each layer of the A layer and the B layer in the first alternating laminate structure is 30 nm or more, the decrease in adhesion due to the residual stress difference between the first alternating laminate and the second alternating laminate is suppressed, and peeling is also suppressed, so that the chipping resistance of the coated cutting tool in both high-speed processing and high-feed processing tends to be further improved. In addition, when the average thickness per layer of layers A and B in the first alternating laminate structure is 300 nm or less, the effect of having the first alternating laminate is exerted and toughness is improved, so that the coated cutting tool tends to have excellent chipping resistance.

[0042] [Third alternate laminated structure] In the coated cutting tool of this embodiment, the coating layer preferably has a third alternating laminate structure in which the first alternating laminate structure and the second alternating laminate structure are alternately formed three or more times in total. In the coated cutting tool of this embodiment, when the coated cutting tool has the third alternating laminate structure, the effect of suppressing the progress of cracks generated during processing into the base material tends to be further improved, and the chipping resistance tends to be further improved in both high-speed processing and high-feed processing.

[0043] In the coated cutting tool of this embodiment, when the coated cutting tool has the third alternating lamination structure, the average thickness per structure of the first alternating lamination structure in the third alternating lamination structure is preferably 0.1 μm or more and 1.5 μm or less. In the coated cutting tool of this embodiment, when the coated cutting tool has the third alternating lamination structure, if the average thickness per structure of the first alternating lamination structure is 0.1 μm or more, the decrease in adhesion due to the residual stress difference between the first alternating lamination structure and the second alternating lamination structure is suppressed, and the chipping resistance tends to be further improved in both high-speed processing and high-feed processing. On the other hand, in the coated cutting tool of this embodiment, when the coated cutting tool has the third alternating lamination structure, if the average thickness per structure of the first alternating lamination structure is 1.5 μm or less, the effect of having the third alternating lamination structure is obtained, and the effect of suppressing the progression of cracks generated during processing to the base material tends to be further improved, and the chipping resistance tends to be further improved in both high-speed processing and high-feed processing. From the same viewpoint, when the third alternating laminate structure is present, the average thickness per structure of the first alternating laminate structure is more preferably 0.2 μm or more and 1.2 μm or less, and further preferably 0.2 μm or more and 1.0 μm or less. In this embodiment, the average thickness per structure of the first alternating laminate structure in the third alternating laminate structure is the total of the average thicknesses of each of the first alternating laminate structures formed in the third alternating laminate structure divided by the number of first alternating laminate structures formed.For example, when the coating layer has a configuration such as "substrate / first alternating laminate structure / second alternating laminate structure / first alternating laminate structure / second alternating laminate structure / first alternating laminate structure / second alternating laminate structure (outermost surface)", the average thickness per structure of each of the three first alternating laminate structures formed in the third alternating laminate structure is the total of the average thicknesses of each of the three first alternating laminate structures formed divided by the number of first alternating laminate structures formed, "3". In addition, in the coated cutting tool of this embodiment, when the coated cutting tool has the third alternating lamination structure, the average thickness per structure of the second alternating lamination structure in the third alternating lamination structure is preferably 0.1 μm or more and 1.5 μm or less. In the coated cutting tool of this embodiment, when the coated cutting tool has the third alternating lamination structure, if the average thickness per structure of the second alternating lamination structure is 0.1 μm or more, the decrease in adhesion due to the residual stress difference between the first alternating lamination structure and the second alternating lamination structure is suppressed, and the chipping resistance tends to be further improved in both high-speed processing and high-feed processing. On the other hand, in the coated cutting tool of this embodiment, when the coated cutting tool has the third alternating lamination structure, if the average thickness per structure of the second alternating lamination structure is 1.5 μm or less, the effect of having the third alternating lamination structure is obtained, and the effect of suppressing the progression of cracks generated during processing to the base material tends to be further improved, and the chipping resistance tends to be further improved in both high-speed processing and high-feed processing. From the same viewpoint, when the third alternating laminate structure is present, the average thickness per structure of the second alternating laminate structure is more preferably 0.2 μm or more and 0.6 μm or less, and further preferably 0.3 μm or more and 0.6 μm or less. In this embodiment, the average thickness per structure of the second alternating laminate structure in the third alternating laminate structure is the total of the average thicknesses of each of the second alternating laminate structures formed in the third alternating laminate structure divided by the number of second alternating laminate structures formed.For example, when the coating layer has a configuration such as "substrate / first alternating laminate structure / second alternating laminate structure / first alternating laminate structure / second alternating laminate structure / first alternating laminate structure / second alternating laminate structure (outermost surface)", the average thickness per structure of each of the three second alternating laminate structures formed in the third alternating laminate structure is the total of the average thicknesses of each of the three second alternating laminate structures formed divided by the number of second alternating laminate structures formed, "3".

[0044] In the coated cutting tool of this embodiment, in the third alternating laminate structure, the number of repetitions of the first alternating laminate structure and the second alternating laminate structure is preferably 1.5 to 45, more preferably 2.5 to 9. In this embodiment, when one each of the first alternating laminate structure and the second alternating laminate structure is formed, the "number of repetitions" is one. Also, when a total of three alternating laminate structures are formed, for example, the first alternating laminate structure / second alternating laminate structure / first alternating laminate structure, the "number of repetitions" is 1.5.

[0045] In the coated cutting tool of this embodiment, when the coating layer has a first alternating laminate structure, in X-ray diffraction of the first alternating laminate structure, it is preferable that the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic (111) plane to the diffraction peak intensity (I(200)) of the cubic (200) plane is 0.5 or more and 5.0 or less. Furthermore, in the coated cutting tool of this embodiment, when the coating layer has a third alternating laminate structure, in X-ray diffraction of the third alternating laminate structure, it is preferable that the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic (111) plane to the diffraction peak intensity (I(200)) of the cubic (200) plane is 0.5 or more and 5.0 or less. In the coated cutting tool of this embodiment, when the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic crystal (200) plane to the diffraction peak intensity (I(200)) of the cubic crystal (111) plane in the X-ray diffraction of the first alternating laminate structure or the third alternating laminate structure is 0.5 or more, the hardness of the coating layer increases, and the wear resistance tends to be excellent. On the other hand, in the coated cutting tool of this embodiment, when the diffraction peak intensity ratio (I(111) / I(200)) is 5.0 or less, the toughness of the coating layer improves, and the chipping resistance tends to be excellent. From the same viewpoint, the diffraction peak intensity ratio (I(111) / I(200)) is more preferably 1.1 or more and 4.8 or less, and even more preferably 1.8 or more and 4.5 or less. In this embodiment, the measurement positions for calculating the diffraction peak intensity ratio are any three points included in the area involved in cutting (it is preferable to select these points at a distance of 0.5 mm or more from each other so that they can represent the stress in the area).

[0046] The peak intensity of each plane index in the coating layer of this embodiment can be obtained by using a commercially available X-ray diffraction device. For example, by using a model: SmartLab X-ray diffraction device manufactured by Rigaku Corporation, X-ray diffraction of a 2θ / θ focusing optical system using Cu-Kα rays is measured under the following conditions, the peak intensity of each plane index can be measured. Here, the measurement conditions are: output: 45 kV, 200 mA, incident side Soller slit: 5°, divergence vertical slit: 2 / 3°, divergence vertical limiting slit: 5 mm, scattering slit 8 mm, light receiving side Soller slit: 5°, light receiving slit: 0.3 mm, sampling width: 0.02°, scan speed: 1° / min, 2θ measurement range: 30° to 90°. When obtaining the peak intensity of each plane index from the X-ray diffraction pattern, analysis software attached to the X-ray diffraction device may be used. In the analysis software, background processing and Kα2 peak removal are performed using a cubic approximation, and profile fitting is performed using a Pearson-VII function to obtain each peak intensity. Specifically, the intensity can be measured and calculated by the method described in the Examples below.

[0047] Fig. 1 is a schematic cross-sectional view showing an example of a coated cutting tool according to this embodiment. The coated cutting tool 1 includes a substrate 2 and a coating layer 3 formed on the surface of the substrate 2. The coating layer 3 has a first alternating laminate structure 4 in which, from the substrate 2 side, an A layer 41 and a B layer 42 are alternately and repeatedly formed. In the first alternating laminate structure shown in Fig. 1, the A layer 41 and the B layer 42 are each alternately and repeatedly formed six times. FIG. 2 is a schematic cross-sectional view showing yet another example of the coated cutting tool of this embodiment. The coated cutting tool 1 includes a substrate 2 and a coating layer 3 formed on the surface of the substrate 2. The coating layer 3 has a third alternating laminate structure 6 in which a first alternating laminate structure 4 and a second alternating laminate structure 5 are alternately and repeatedly formed in sequence from the substrate 2 side. The first alternating laminate structure 4 is formed by alternately and repeatedly forming an A layer 41 and a B layer 42 in sequence from the substrate 2 side. The second alternating laminate structure 5 is formed by alternately and repeatedly forming an A layer 51 and a C layer 52 in sequence from the substrate 2 side. In the third alternating laminate structure shown in FIG. 2, the first alternating laminate structure 4 and the second alternating laminate structure 5 are alternately and repeatedly formed twice.

[0048] Bottom Layer The coating layer used in this embodiment may be composed of only the first alternating laminate structure or the third alternating laminate structure described above, but it is preferable to have a lower layer between the substrate and the first alternating laminate structure or the third alternating laminate structure. By having a lower layer, the adhesion between the substrate and the coating layer tends to be further improved. From the same viewpoint, the lower layer is preferably a single layer or multiple layers of a compound consisting of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, B, and Y, and at least one element selected from the group consisting of C, N, O, and B (however, the composition of the compound constituting the lower layer is different from the composition of the compound constituting the layer of the first alternating laminate structure or the second alternating laminate structure in contact with the lower layer), and is preferably selected from the group consisting of Ti, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y. and at least one element selected from the group consisting of C, N, O, and B, more preferably a single layer or multilayer of a compound consisting of at least one element selected from the group consisting of Ti, Ta, Cr, Mo, W, Al, Si, and Y, and at least one element selected from the group consisting of N and B, and particularly preferably a single layer or multilayer of a compound consisting of at least one element selected from the group consisting of Ti, Cr, Mo, and Al, and N. Specific compounds contained in the lower layer are not particularly limited, but examples include TiMoN, CrN, TiAlCrN, TiAlN, TiN, TiCN, and AlCrN.

[0049] In the coated cutting tool of this embodiment, the average thickness of the lower layer is preferably 0.01 μm or more and 2.00 μm or less. In the coated cutting tool of this embodiment, if the average thickness of the lower layer is 0.01 μm or more, the adhesion between the coating layer and the substrate tends to be further improved, and the chipping resistance tends to be further improved in both high-speed processing and high-feed processing. On the other hand, in the coated cutting tool of this embodiment, if the average thickness of the lower layer is 2.00 μm or less, peeling of the coating layer is suppressed, and the chipping resistance tends to be further improved in both high-speed processing and high-feed processing. From the same viewpoint, the average thickness of the lower layer is more preferably 0.02 μm or more and 1.00 μm or less, and even more preferably 0.10 μm or more and 0.50 μm or less.

[0050] [Top layer] The coating layer used in this embodiment may be composed of only the first alternating laminate structure or the third alternating laminate structure described above, but may have an upper layer on the surface of the first alternating laminate structure or the third alternating laminate structure opposite to the substrate. The upper layer is preferably a single layer or multiple layers of a compound having a composition represented by the compound formulas (1) to (3) consisting of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and at least one element selected from the group consisting of C, N, O, and B (however, the composition of the compound constituting the upper layer is different from the composition of the compound constituting the layer of the first alternating laminate structure or the second alternating laminate structure that is in contact with the upper layer). When the upper layer is a single layer or multiple layers of the above-mentioned compounds, the wear resistance tends to be more excellent. From the same viewpoint, the upper layer preferably contains a compound consisting of at least one element selected from the group consisting of Ti, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and at least one element selected from the group consisting of C, N, O, and B, more preferably contains a compound consisting of at least one element selected from the group consisting of Ti, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and at least one element selected from the group consisting of N and B, and particularly preferably contains a compound consisting of at least one element selected from the group consisting of Ti, Nb, Mo, Al, and Si, and at least one element selected from the group consisting of N and B. Specific compounds contained in the upper layer are not particularly limited, but examples thereof include TiN, TiAlN, TiSiN, TiMoN, NbN, and TiAlBN. The upper layer may be a single layer or a multilayer of two or more layers.

[0051] In the coated cutting tool of this embodiment, the average thickness of the upper layer is preferably 0.01 μm or more and 2.00 μm or less. In the coated cutting tool of this embodiment, when the average thickness of the upper layer is 0.01 μm or more, the wear resistance tends to be excellent in high-speed machining. On the other hand, in the coated cutting tool of this embodiment, when the average thickness of the upper layer is 2.00 μm or less, peeling of the coating layer is suppressed, and the chipping resistance tends to be further improved in both high-speed machining and high-feed machining. From the same viewpoint, the average thickness of the upper layer is more preferably 0.20 μm or more and 1.50 μm or less, and even more preferably 0.50 μm or more and 1.50 μm or less.

[0052] [Method of manufacturing the coating layer] The method for producing the coating layer in the coated cutting tool of this embodiment is not particularly limited, but examples thereof include physical vapor deposition methods such as ion plating, arc ion plating, sputtering, and ion mixing. When the coating layer is formed using a physical vapor deposition method, a sharp edge can be formed, which is preferable. Among them, the arc ion plating method is more preferable because it provides better adhesion between the coating layer and the substrate.

[0053] [Method of manufacturing coated cutting tools] The method for producing the coated cutting tool of this embodiment will be described below using a specific example. Note that the method for producing the coated cutting tool of this embodiment is not particularly limited as long as the configuration of the coated cutting tool can be achieved.

[0054] First, the substrate processed into the tool shape is placed in the reaction vessel of the physical vapor deposition device, and the metal evaporation source is placed in the reaction vessel. Then, the pressure in the reaction vessel is increased to 1.0×10 -2The reaction vessel is evacuated to a vacuum of 1.0 Pa or less, and the substrate is heated by a heater in the reaction vessel until its temperature reaches 200°C to 700°C. After heating, Ar gas is introduced into the reaction vessel to set the pressure inside the reaction vessel to 0.5 Pa to 5.0 Pa. In an Ar gas atmosphere with a pressure of 0.5 Pa to 5.0 Pa, a bias voltage of -500 V to -350 V is applied to the substrate, and a current of 40 A to 50 A is passed through the tungsten filament in the reaction vessel to perform an ion bombardment treatment with Ar gas on the surface of the substrate. After the ion bombardment treatment has been performed on the surface of the substrate, the pressure inside the reaction vessel is increased to 1.0 x 10 -2 The vacuum is drawn until the vacuum pressure reaches or exceeds 1 Pa.

[0055] When forming the lower layer used in this embodiment, the base material is controlled until its temperature reaches 300°C to 500°C. After the control, gas is introduced into the reaction vessel to set the pressure in the reaction vessel to 3.0 Pa to 5.0 Pa. As the gas, for example, when the lower layer is composed of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and a compound consisting of N, N2 gas can be used, and when the lower layer is composed of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and a compound consisting of N and C, N2 gas and C2H2 gas can be used. The volume ratio of the mixed gas is not particularly limited, but may be, for example, N2 gas:C2H2 gas=95:5 to 85:15. Next, a bias voltage of −120V to −30V is applied to the substrate, and a metal evaporation source according to the metal component of each layer is evaporated by arc discharge with an arc current of 80A to 150A to form a lower layer.

[0056] When forming the A layer of the first and second alternating laminate structures used in this embodiment, the temperature of the base material is controlled to 300°C to 500°C, N2 gas is introduced into the reaction vessel, and the pressure inside the reaction vessel is set to 3.0 Pa to 5.0 Pa. Thereafter, a bias voltage of -80 V to -40 V is applied to the base material, and a metal evaporation source according to the metal component of the A layer is evaporated by arc discharge at 80 A to 150 A, to form the A layer.

[0057] When forming the B layer of the first alternating laminate structure and the C layer of the second alternating laminate structure used in this embodiment, the temperature of the base material is controlled to 300°C to 500°C. It is preferable to make the temperature of the base material the same as that of the base material when forming the A layer, since the A layer and the B layer, or the A layer and the C layer can be formed continuously. After controlling the temperature, N2 gas is introduced into the reaction vessel, and the pressure in the reaction vessel is set to 3.0 Pa to 5.0 Pa. Next, a bias voltage of -80V to -40V is applied to the base material, and a metal evaporation source according to the metal component of the B layer or the C layer is evaporated by arc discharge with an arc current of 80A to 150A to form the B layer or the C layer.

[0058] To form a first alternating laminate structure in which two or more layers of A and two or more layers of B are alternately laminated, each layer may be formed alternately by evaporating a metal evaporation source corresponding to the metal component of layer A and a metal evaporation source corresponding to the metal component of layer B by arc discharge under the above-mentioned conditions. The thickness of each layer constituting the alternating laminate structure can be controlled by adjusting the arc discharge time of the metal evaporation source corresponding to the metal component of layer A and the metal evaporation source corresponding to the metal component of layer B. The same applies to the case where a second alternate laminate structure is formed in which two or more layers of A and two or more layers of C are alternately laminated.

[0059] In order to set the composition of the entire compound in the alternating laminate structure used in this embodiment and the atomic ratios ((1-ab) / d) and ((a+c) / 2) to predetermined values, it is advisable to adjust the thickness of each layer in the alternating laminate structure and the ratio of metal elements in each layer in the process of forming the above-mentioned alternating laminate structure.

[0060] In order to set the X-ray diffraction peak intensity ratio (I(111) / I(200)) of the coating layer used in this embodiment to a predetermined value, it is advisable to adjust the temperature of the substrate, the bias voltage, or the pressure in the reaction vessel in the process of forming the above-mentioned alternate laminate structure. More specifically, in the process of forming the alternate laminate structure, if the temperature of the substrate is lowered, the negative bias voltage is increased (in the direction away from zero), or the pressure in the reaction vessel is lowered, the X-ray diffraction peak intensity ratio (I(111) / I(200)) tends to increase.

[0061] When forming the upper layer used in this embodiment, it is preferable to form it under the same manufacturing conditions as the lower layer described above. That is, first, the base material is controlled until its temperature reaches 300°C to 500°C. After the control, gas is introduced into the reaction vessel to set the pressure in the reaction vessel to 3.0 Pa to 5.0 Pa. As the gas, for example, when the upper layer is composed of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y and a compound consisting of N, N2 gas can be used, and when the upper layer is composed of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y and a compound consisting of N and C, N2 gas and C2H2 gas can be used. The volume ratio of the mixed gas is not particularly limited, but may be, for example, N2 gas:C2H2 gas=95:5 to 85:15. Next, a bias voltage of −120V to −30V is applied to the base material, and a metal evaporation source according to the metal component of each layer is evaporated by arc discharge with an arc current of 80A to 150A to form the upper layer.

[0062] The thickness of each layer constituting the coating layer in the coated cutting tool of this embodiment can be measured from the cross-sectional structure of the coated cutting tool using an optical microscope, a scanning electron microscope (SEM), a transmission electron microscope (TEM), etc. The average thickness of each layer in the coated cutting tool of this embodiment can be determined by measuring the thickness of each layer from three or more cross sections in the vicinity of a position 50 μm from the cutting edge of the surface facing the metal evaporation source toward the center of the surface, and calculating the average value (arithmetic mean value).

[0063] In addition, the composition of each layer constituting the coating layer in the coated cutting tool of this embodiment can be measured from the cross-sectional structure of the coated cutting tool of this embodiment using an energy dispersive X-ray analyzer (EDS) or a wavelength dispersive X-ray analyzer (WDS), for example.

[0064] The coated cutting tool of this embodiment is considered to have the effect of extending the tool life in both high-speed machining and high-feed machining, as compared with conventional tools (however, the factors that enable the tool life to be extended are not limited to those mentioned above). Specific examples of the types of the coated cutting tool of this embodiment include indexable cutting inserts for milling or turning, drills, and end mills. EXAMPLES

[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0066] Example 1 A cemented carbide alloy with a composition of 86.0% WC-12.0% Co-1.0% NbC-1.0% Cr3C2 (all mass%) processed into an SNMU1307ANEN-MJ insert shape (manufactured by Tungaloy Corporation) was prepared as the substrate. A metal evaporation source was placed in the reaction vessel of the arc ion plating device so as to obtain the compound layer composition shown in Tables 1 and 2. The prepared substrate was fixed to the fixture of the rotary table in the reaction vessel.

[0067] After that, the pressure in the reaction vessel was increased to 5.0 × 10 -3 The reaction vessel was evacuated to a vacuum of 450° C. or less. After evacuation, the substrate was heated by a heater in the reaction vessel until its temperature reached 450° C. After heating, Ar gas was introduced into the reaction vessel so that the pressure became 2.7 Pa.

[0068] In an Ar gas atmosphere at a pressure of 2.7 Pa, a bias voltage of -400 V was applied to the substrate, and a current of 40 A was passed through the tungsten filament in the reaction vessel, and ion bombardment treatment with Ar gas was performed on the surface of the substrate for 30 minutes. After the ion bombardment treatment was completed, the pressure in the reaction vessel was increased to 5.0 × 10 -3 The vacuum was pulled until the vacuum reached 0.1 Pa or less.

[0069] For the invention products 1 to 37 and the comparative products 1 to 22, after evacuation, the temperature of the substrate was controlled to be the temperature shown in Tables 3 and 4 (temperature at the start of film formation), nitrogen gas (N2) was introduced into the reaction vessel, and the pressure inside the reaction vessel was adjusted to be the pressure shown in Tables 3 and 4. Thereafter, the bias voltage shown in Tables 3 and 4 was applied to the substrate, and the metal evaporation sources of the A layer and the B layer having the compositions shown in Tables 1 and 2 were evaporated alternately in this order by arc discharge with the arc current shown in Tables 3 and 4, and the A layer and the B layer were formed alternately on the surface of the substrate in this order. At this time, the pressure inside the reaction vessel was controlled to be the pressure shown in Tables 3 and 4. In addition, the thicknesses of the A layer and the B layer were controlled by adjusting the respective arc discharge times so as to be the thicknesses shown in Tables 1 and 2.

[0070] After a compound layer was formed on the surface of the substrate to the specified average thickness shown in Tables 1 and 2, the heater was turned off, and after the sample temperature reached 100°C or lower, the sample was removed from the reaction vessel.

[0071] The average thickness of each compound layer of the obtained sample was obtained by observing three cross sections using TEM in the vicinity of a position 50 μm from the cutting edge ridge of the surface facing the metal evaporation source toward the center of the surface, measuring the thickness of the compound layer, and calculating the average value (arithmetic mean value). The average thickness per layer of A was calculated by dividing the total thickness obtained by adding up the thicknesses of each A layer by the number of A layers (repetition number). Similarly, the average thickness per layer of B was calculated by dividing the total thickness obtained by adding up the thicknesses of each B layer by the number of B layers (repetition number). The results are shown in Tables 1 and 2.

[0072] The composition of each compound layer of the obtained samples was measured using an EDS attached to a TEM on a cross section in the vicinity of a position 50 μm from the cutting edge of the surface facing the metal evaporation source of the coated cutting tool toward the center. The results are also shown in Tables 1 and 2.

[0073] [Table 1]

[0074] [Table 2]

[0075] [Table 3]

[0076] [Table 4]

[0077] The ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic crystal (200) plane to the diffraction peak intensity (I(200)) of the cubic crystal (111) plane in the alternating stack structure of the obtained sample was measured using an X-ray diffraction device, model: SmartLab, manufactured by Rigaku Corporation. Specifically, the X-ray diffraction measurement of the 2θ / θ focusing optical system using Cu-Kα radiation was performed under the following conditions: output: 45 kV, 200 mA, incident side Soller slit: 5°, divergence vertical slit: 2 / 3°, divergence vertical limiting slit: 5 mm, scattering slit: 8 mm, light receiving side Soller slit: 5°, light receiving slit: 0.3 mm, sampling width: 0.02°, scan speed: 1° / min, 2θ measurement range: 30 to 90°. The peak intensity (I(200)) of the cubic crystal (200) plane of the alternating laminate structure and the peak intensity (I(111)) of the cubic crystal (111) plane of the alternating laminate structure were measured, and the ratio (I(111) / I(200)) was calculated. The results are shown in Tables 5 and 6. When determining the peak intensity of each of the above plane indexes from the X-ray diffraction pattern, analysis software attached to the X-ray diffraction device was used. In the analysis software, background processing and Kα2 peak removal were performed using a cubic approximation, and profile fitting was performed using the Pearson-VII function to obtain each peak intensity. The crystal system of the alternating stack structure was also confirmed by X-ray diffraction measurement. More specifically, the peak intensities of the cubic (200) and cubic (111) planes of the alternating stack structure were measured as the measurement targets. In this case, the peak intensity including both reflections was obtained instead of separating the peaks of the A layer and the B layer. For convenience, the above ratio (I(111) / I(200)) was calculated from the peak intensities obtained in this way.

[0078] [Table 5]

[0079] [Table 6]

[0080] The obtained samples were subjected to the following cutting test and evaluated.

[0081] [Cutting test] (Cutting test condition 1) High speed machining Work material: SUS304, Cutting material shape: 200mm x 150mm x 70mm plate, Cutting speed: 250m / min, Feed per tooth: 0.1mm / tooth, Cutting depth: 2.0mm, Cutting width: 70mm, Coolant: Not used, Evaluation item: The machining time until the tool flank wear width reaches 0.3 mm or the cutting edge is chipped is defined as the tool life. The longer the machining time until the tool life is reached, the better the chipping resistance and wear resistance. The obtained evaluation results are shown in Tables 7 and 8. In Tables 7 and 8, for tool life under cutting test condition 1, 30 minutes or more is rated as "A", 20 minutes or more but less than 30 minutes is rated as "B", and less than 20 minutes is rated as "C". In addition, in Tables 7 and 8, for "damage", if the flank wear width reaches 0.3 mm and the tool life is over, it is shown as "normal wear", and if the cutting edge is chipped and the tool life is over, it is shown as "chip".

[0082] (Cutting test condition 2) High feed rate machining Work material: SCM440, Cutting material shape: 200mm x 150mm x 25mm plate, Cutting speed: 150m / min, Feed per tooth: 0.3mm / tooth, Cutting depth: 2.0mm, Cutting width: 25mm, Coolant:Use, Evaluation item: The machining time until the cutting edge is chipped is defined as the tool life. The longer the machining time until the tool life is reached, the more excellent the chipping resistance and wear resistance are. The obtained evaluation results are shown in Tables 7 and 8. In Tables 7 and 8, for the tool life under cutting test condition 2, a rating of "A" is given for tool life of 25 minutes or more, a rating of "B" is given for tool life of 20 minutes or more but less than 25 minutes, and a rating of "C" is given for tool life of less than 20 minutes.

[0083] [Table 7]

[0084] [Table 8]

[0085] From the results shown in Tables 7 and 8, it can be seen that the inventive products were rated "B" or higher under both cutting test condition 1 and cutting test condition 2, did not receive a rating of "C," and had better chipping resistance and wear resistance than the comparative products, resulting in a longer tool life.

[0086] Example 2 As the substrate, a cemented carbide alloy having a composition of 86.0% WC-12.0% Co-1.0% NbC-1.0% Cr3C2 (all mass%) processed into an insert shape of SNMU1307ANEN-MJ (manufactured by Tungaloy Corporation) was prepared. A specified metal evaporation source was placed in the reaction vessel of the arc ion plating device. The prepared substrate was fixed to the fixture of the rotating table in the reaction vessel.

[0087] After that, the pressure in the reaction vessel was increased to 5.0 × 10 -3 The reaction vessel was evacuated to a vacuum of 450° C. or less. After evacuation, the substrate was heated by a heater in the reaction vessel until its temperature reached 450° C. After heating, Ar gas was introduced into the reaction vessel so that the pressure became 2.7 Pa.

[0088] In an Ar gas atmosphere at a pressure of 2.7 Pa, a bias voltage of -400 V was applied to the substrate, and a current of 40 A was passed through the tungsten filament in the reaction vessel, and ion bombardment treatment with Ar gas was performed on the surface of the substrate for 30 minutes. After the ion bombardment treatment was completed, the pressure in the reaction vessel was increased to 5.0 × 10 -3 The vacuum was pulled until the vacuum reached 0.1 Pa or less.

[0089] After evacuation, the first alternating laminate structure and the second alternating laminate structure were alternately formed on the surface of the substrate as shown in Tables 9 and 10. The manufacturing conditions of the first alternating laminate structure were the same as the manufacturing conditions of each invention shown in the "Composition" column of Tables 9 and 10. However, the average thickness per layer of each layer, the number of repetitions and average thickness per structure, and the total average thickness were as shown in Tables 9 and 10. The second alternating laminate structure (types A to G) was manufactured as follows with the composition shown in Table 11 and the manufacturing conditions shown in Table 12. After evacuation, the temperature of the substrate was controlled to be the temperature shown in Table 12 (temperature at the start of film formation), nitrogen gas (N2) was introduced into the reaction vessel, and the pressure inside the reaction vessel was adjusted to be the pressure shown in Table 12. Thereafter, a bias voltage shown in Table 12 was applied to the substrate, and metal evaporation sources for A layer and C layer having the composition shown in Table 11 were alternately evaporated in this order by arc discharge with an arc current shown in Table 12, to form A layer and C layer alternately in this order on a predetermined surface. At this time, the pressure inside the reaction vessel was controlled to be as shown in Table 12. The thicknesses of A layer and C layer were controlled by adjusting the respective arc discharge times so as to be the thicknesses shown in Tables 9 and 10. Basically, the structures were formed in the order of first alternating laminate structure / second alternating laminate structure / first alternating laminate structure / second alternating laminate structure from the substrate side, but invention products 44, 54, and 55, which have an "*" after the number in the "repetition number" column in Table 10, were formed in the order of second alternating laminate structure / first alternating laminate structure / second alternating laminate structure / first alternating laminate structure from the substrate side. Invention products 43 to 65 shown in Table 10 had a third alternating laminate structure in which the first alternating laminate structure and the second alternating laminate structure were alternately formed three or more times in total (repetition number 1.5 or more).

[0090] After forming the prescribed coating layers shown in Tables 9 and 10 on the surface of the substrate, the heater was turned off, and after the sample temperature had fallen to 100° C. or less, the sample was removed from the reaction vessel.

[0091] The average thickness and composition of each layer of the obtained sample were measured and calculated in the same manner as in Example 1. The results are shown in Tables 1 and 11. In addition, the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic crystal (111) plane to the diffraction peak intensity (I(200)) of the cubic crystal (200) plane in the alternating laminate structure of the obtained sample was also measured and calculated in the same manner as in Example 1. The results are shown in Table 13. In this example, since the peaks of the first alternating laminate structure and the second alternating laminate structure overlapped, the peaks were not separated and were calculated as the peak intensity including both reflections.

[0092] [Table 9]

[0093] [Table 10]

[0094] [Table 11]

[0095] [Table 12]

[0096] [Table 13]

[0097] Using the obtained samples, cutting tests were carried out in the same manner as in Example 1 to evaluate the inventive products. The results are shown in Table 14.

[0098] [Table 14]

[0099] From the results shown in Table 14, it can be seen that the invention product including the second alternating laminate structure has even better chipping resistance and wear resistance, and has a longer tool life.

[0100] Example 3 As the substrate, a cemented carbide alloy having a composition of 86.0% WC-12.0% Co-1.0% NbC-1.0% Cr3C2 (all mass%) processed into an insert shape of SNMU1307ANEN-MJ (manufactured by Tungaloy Corporation) was prepared. A specified metal evaporation source was placed in the reaction vessel of the arc ion plating device. The prepared substrate was fixed to the fixture of the rotating table in the reaction vessel.

[0101] After that, the pressure in the reaction vessel was increased to 5.0 × 10 -3 The reaction vessel was evacuated to a vacuum of 450° C. or less. After evacuation, the substrate was heated by a heater in the reaction vessel until its temperature reached 450° C. After heating, Ar gas was introduced into the reaction vessel so that the pressure became 2.7 Pa.

[0102] In an Ar gas atmosphere at a pressure of 2.7 Pa, a bias voltage of -400 V was applied to the substrate, and a current of 40 A was passed through the tungsten filament in the reaction vessel, and ion bombardment treatment with Ar gas was performed on the surface of the substrate for 30 minutes. After the ion bombardment treatment was completed, the pressure in the reaction vessel was increased to 5.0 × 10 -3 The vacuum was pulled until the vacuum reached 0.1 Pa or less.

[0103] For Inventions 66 to 72, after evacuation, the temperature of the substrate was controlled until it reached the temperature shown in Table 16 (the temperature at the start of film formation), N2 gas was introduced into the reaction vessel, and the pressure inside the reaction vessel was adjusted to the pressure shown in Table 16. Thereafter, a bias voltage shown in Table 16 was applied to the substrate, and the metal evaporation source having the composition of the lower layer shown in Table 15 was evaporated by arc discharge with the arc current shown in Table 16, forming a lower layer having the average thickness shown in Table 15 on the surface of the substrate.

[0104] Next, for invention products 66 to 72 and 76, an alternating laminate structure was formed on the surface of the lower layer as shown in Table 15. Specifically, for invention product 66, the first alternating laminate structure was formed on the surface of the lower layer under the same conditions as invention product 1, for invention product 67, the first alternating laminate structure was formed on the surface of the lower layer under the same conditions as invention product 18, for invention product 68, the first alternating laminate structure was formed on the surface of the lower layer under the same conditions as invention product 19, for invention product 69, the third alternating laminate structure was formed on the surface of the lower layer under the same conditions as invention product 64, and for invention product 71 to 72, the third alternating laminate structure was formed on the surface of the lower layer under the same conditions as invention product 64. For invention product 76, the third alternating laminate structure was formed on the surface of the lower layer under the same conditions as invention product 51. For invention products 73 to 75, an alternating laminate structure was formed on the surface of the substrate as shown in Table 15. Specifically, for invention product 73, a third alternating laminate structure having an average thickness shown in Table 15 was formed on the surface of the substrate under the same conditions as for invention product 64. For invention products 74 to 75, an alternating laminate structure having an average thickness shown in Table 15 was formed on the surface of the substrate under the same conditions as for invention product 38.

[0105] Next, for Invention Products 67-68 and 72-76, after evacuation, the temperature of the substrate was controlled until it reached the temperature shown in Table 16 (the temperature at the start of film formation), N2 gas was introduced into the reaction vessel, and the pressure inside the reaction vessel was adjusted to the pressure shown in Table 16. Thereafter, a bias voltage shown in Table 16 was applied to the substrate, and the metal evaporation source having the composition of the upper layer shown in Table 15 was evaporated by arc discharge with the arc current shown in Table 16, forming an upper layer on the surface of the alternating laminate structure.

[0106] After forming a coating layer as shown in Table 15 on the surface of the substrate, the heater was turned off, and after the sample temperature had dropped to 100° C. or less, the sample was removed from the reaction vessel.

[0107] The average thickness and composition of each layer of the obtained sample were measured and calculated in the same manner as in Example 1. The results are shown in Tables 1, 9, 10, 11, and 15. In addition, the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic (111) plane to the diffraction peak intensity (I(200)) of the cubic (200) plane in the alternating laminate structure of the obtained sample was also measured and calculated in the same manner as in Example 1. The results are shown in Table 17. In this example, when the coating layer is made of the first alternating laminate structure, the peak intensities of the cubic (200) plane and the cubic (111) plane of the first alternating laminate structure were measured, and when the coating layer is the third alternating laminate including both the first alternating laminate and the second alternating laminate, the peak intensities of the cubic (200) plane and the cubic (111) plane of the third alternating laminate were measured. In addition, since the peaks of the first and second alternating laminate structures overlapped, the peaks were not separated, and the peak intensity including both reflections was obtained. In addition, during the measurement, the peaks of the alternating laminate structures were identified by the following methods (i) to (iii). (i) When the coating layer had an upper layer, the upper layer was removed by buffing to identify the peak of the alternating laminate structure. (ii) When the coating layer had a lower layer, the peak of the layer-by-layer structure was identified by thin-film X-ray diffraction method so as not to be influenced by the lower layer. (iii) When the coating layer had an upper layer and a lower layer, the peak of the alternating laminate structure was identified by combining the above (i) and (ii).

[0108] [Table 15]

[0109] [Table 16]

[0110] [Table 17]

[0111] Using the obtained samples, cutting tests were carried out in the same manner as in Example 1 to evaluate the inventive products. The results are shown in Table 18.

[0112] [Table 18]

[0113] The results shown in Table 18 show that the invention including the underlayer and / or overlayer has better chipping and wear resistance and longer tool life. [Industrial Applicability]

[0114] INDUSTRIAL APPLICABILITY The coated cutting tool of the present invention has excellent wear resistance and fracture resistance, and therefore can extend the tool life as compared with conventional tools. [Explanation of symbols]

[0115] 1...Coated cutting tool, 2...Base material, 3...Coating layer, 4...First alternately laminated structure, 41...A layer, 42...B layer, 5...Second alternately laminated structure, 51...A layer, 52...C layer, 6...Third alternately laminated structure.

Claims

1. A coated cutting tool comprising a substrate and a coating layer formed on the substrate, The coating layer has a first alternating laminate structure in which two or more A layers and two or more B layers are alternately formed, The layer A contains a compound having a composition represented by the following formula (1): (Al a Cr b Ti 1-a-b )N (1) (In formula (1), a is the content ratio (atomic ratio) of Al element with respect to the total content of Al element, Cr element, and Ti element, 0.50≦a≦0.68 is satisfied, b is the content (atomic ratio) of Cr element with respect to the total content of Al element, Cr element, and Ti element, 0.02≦b≦0.30 is satisfied, 1-a-b is the content ratio (atomic ratio) of Ti element to the total content of Al element, Cr element, and Ti element, Satisfies 0.11≦1-a-b≦0.40.) The layer B contains a compound having a composition represented by the following formula (2): <h2 style=";text-align:left;direction:ltr">((Al<h2 style=";text-align:left;direction:ltr"> c <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 1-c-d <h2 style=";text-align:left;direction:ltr"> B<h2 style=";text-align:left;direction:ltr"> d <h2 style=";text-align:left;direction:ltr"> ()N(22) (In formula (2), c is the content ratio (atomic ratio) of Al element to the total content of Al element, Ti element, and B element, 0.30≦c≦0.64 is satisfied, d is the content ratio (atomic ratio) of B element to the total content of Al element, Ti element and B element, 0.01≦d≦0.10 is satisfied, 1-c-d is the content ratio (atomic ratio) of Ti element to the total content of Al element, Ti element, and B element, 0.30≦1−c−d≦0.69 is satisfied.) The average thickness of the first alternating laminate structure is 0.50 μm or more and 10.00 μm or less, The average thickness of each of the A layers in the first alternating laminate structure is 2 nm or more and 300 nm or less, The average thickness per layer of the B layer in the first alternating laminate structure is 2 nm or more and 300 nm or less. Coated cutting tools.

2. a ratio ((1-a-b) / d) of a content ratio (atomic ratio) of Ti element in the A layer to a content ratio (atomic ratio) of B element in the B layer is 2.0 or more and 25.0 or less; The coated cutting tool of claim 1 .

3. the average value ((a+c) / 2) of the content ratio (atomic ratio) of Al element in the A layer and the content ratio (atomic ratio) of Al element in the B layer is 0.50 or more and 0.62 or less; The coated cutting tool according to claim 1 or 2.

4. The coating layer further has a second alternating laminate structure in which the A layer and the C layer are alternately formed in two or more layers, The C layer contains a compound having a composition represented by the following formula (3): <h2 style=";text-align:left;direction:ltr">((Al<h2 style=";text-align:left;direction:ltr"> e <h2 style=";text-align:left;direction:ltr"> Ti<h2 style=";text-align:left;direction:ltr"> 1-e <h2 style=";text-align:left;direction:ltr"> ()N(3) (In formula (3), e is the content ratio (atomic ratio) of Al element to the total of Al element and Ti element, 0.30≦e≦0.64 is satisfied, 1-e is the content ratio (atomic ratio) of Ti element to the total of Al element and Ti element, 0.36≦1-e≦0.70 is satisfied.) The average thickness of the second alternating laminate structure is 0.50 μm or more and 5.00 μm or less, the average thickness per layer of the A layer in the second alternate laminate structure is 2 nm or more and less than 30 nm; The average thickness per layer of the C layer in the second alternating laminate structure is 2 nm or more and less than 30 nm. The coated cutting tool of claim 1 .

5. The average thickness of each of the A layers in the first alternating laminate structure is 30 nm or more and 300 nm or less, The average thickness of each of the B layers in the first alternating laminate structure is 30 nm or more and 300 nm or less. The coated cutting tool according to claim 1 or 2.

6. The coating layer has a third alternating laminate structure in which the first alternating laminate structure and the second alternating laminate structure are alternately formed three or more times in total, The average thickness per structure of the first alternating laminate structure in the third alternating laminate structure is 0.1 μm or more and 1.5 μm or less, The average thickness per structure of the second alternating laminate structure in the third alternating laminate structure is 0.1 μm or more and 1.5 μm or less. The coated cutting tool of claim 4.

7. In the X-ray diffraction of the first alternating stack structure, the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic (111) plane to the diffraction peak intensity (I(200)) of the cubic (200) plane is 0.5 or more and 5.0 or less. The coated cutting tool according to claim 1 or 2.

8. In the X-ray diffraction of the third alternating stack structure, the ratio (I(111) / I(200)) of the diffraction peak intensity (I(111)) of the cubic (200) plane to the diffraction peak intensity (I(200)) of the cubic (111) plane is 0.5 or more and 5.0 or less. The coated cutting tool of claim 6.

9. The coating layer has an upper layer on a surface of the first alternating laminate structure or the third alternating laminate structure opposite to the substrate, the upper layer is a single layer or multiple layers of a compound consisting of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and at least one element selected from the group consisting of C, N, O, and B (wherein the composition of the compound constituting the upper layer is different from the composition of the compound constituting the layer of the first alternating laminate structure or the second alternating laminate structure that is in contact with the upper layer); The average thickness of the upper layer is 0.01 μm or more and 2.00 μm or less. The coated cutting tool according to claim 1 or 6.

10. The coating layer has a lower layer between the substrate and the first alternating laminate structure or the third alternating laminate structure, the lower layer is a single layer or multiple layers of a compound consisting of at least one element selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Al, Si, and Y, and at least one element selected from the group consisting of C, N, O, and B (with the proviso that the composition of the compound constituting the lower layer is different from the composition of the compound constituting the layer of the first alternating laminate structure or the second alternating laminate structure in contact with the lower layer); The average thickness of the lower layer is 0.01 μm or more and 2.00 μm or less. The coated cutting tool according to claim 1 or 6.

11. The average thickness of the entire coating layer is 0.5 μm or more and 10.0 μm or less. The coated cutting tool according to claim 1 or 2.

Citation Information

Patent Citations

  • Surface coated cutting tool having hard coating layer exhibiting excellent wear resistance in high-speed cutting heat resisting alloy

    JP2007152457A

  • Coating member

    JP2009203485A

  • Surface-coated cutting tool

    JP2011224671A

  • Coated cutting tool

    JP2023086393A

  • Hard coating for cutting tool

    US20180245201A1

Cited By

  • Cutting tool deposited with multiple nano-composite coatings and preparation method of cutting tool

    CN122105326A